The Role of the PI3K/AKT/mTOR Signaling Axis in the Decision of the Celastrol-Induced Cell Death Mechanism Related to the Lipid Regulatory Pathway in Prostate Cancer Cells - RENCÜZOĞULLARI, ÖZGE; Çoban, Mervenur; Sevgin, Bortecine; Çoker-Gürkan, Ajda; YERLİKAYA, PINAR OBAKAN; Palavan-Ünsal, Narcin; ARISAN, ELİF DAMLA (Elsevier, 2020)
Prostate cancer is one of the leading cancer types among the male population worldwide, with high incidence and mortality rates. Celastrol is a promising bioactive component extracted from Tripterygium wilfordi. Celastrol is a multimodal agent with therapeutic advantages, with activities that affect cell proliferation, inflammation (through affecting proteotoxic stress) and cell death mechanisms such as autophagy, apoptosis and paraptosis. Celastrol alters the PI3K/AKT signaling axis to suppress the cell viability of cancer cells. Although a number of celastrol targets have been identified in cancer cells, the genomic differences in malignant cells prevent the efficacy of celastrol. Therefore, new studies are required to highlight its potential therapeutic effects in cancer cells. In this study, we investigated the therapeutic potential of celastrol in LNCaP, DU145 and PC3 prostate cancer cells. According to our results, celastrol decreased cell viability in a dose-dependent manner in the cells. LNCaP prostate cancer cells were more sensitive to celastrol treatment compared to DU145 and PC3 cells. We found that celastrol modulated PI3K/AKT/mTOR signaling to alter lipid regulatory pathways by affecting LAMP -1 and lipin-1 in PC3 cells. Although celastrol downregulated FASN in all cell lines, active mTOR signaling led to altered responses in prostate cancer cells by affecting the cellular fate decision pathways.
Keywords: Celastrol; Apoptosis; Autophagy; PI3K/AKT/mTOR Signaling Axis; LAMP-1; Prostate Cancer